500mpa grade natural aging resistant enhanced formability hot dip galvanized dual phase steel and method of making

CN122979755APending Publication Date: 2026-10-27SHOUGANG GROUP CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611391960.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-09
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

现有技术方案往往仅侧重其中一两个方面,难以系统解决热镀锌双相钢在仓储、运输至冲压前的时效过程中力学性能波动的问题,易导致冲压稳定性下降与表面缺陷风险,制约了该类钢在高表面要求外板上的规模化应用

Benefits of technology

本申请实施例提供了500MPa级抗自然时效的增强成形性热镀锌双相钢及制备方法,以质量分数计,所述热镀锌双相钢的化学成分为:C:0.06%~0.12%,Si:0.20%~0.50%,Mn:1.05%~1.55%,Cr:0.20%~0.60%,Al:0.30%~0.70%,P≤0.015%,S≤0.0025%,其余为Fe及不可避免的杂质;所述热镀锌双相钢的显微组织以铁素体为基体,马氏体及贝氏体作为主要的硬质强化相,同时含有体积分数不大于8%的残余奥氏体;在所述铁素体的晶界以及所述铁素体与残余奥氏体和/或马氏体的相界上,弥散分布有碳化物;所述碳化物的尺寸≤0.3μm。在成分设计方面,0.06wt%~0.12wt%的碳与0.20wt%~0.60wt%的铬为抗自然时效提供了基础。适量的碳是保证热镀锌双相钢强度的必要元素。添加的铬能够与碳结合,在后续工艺中形成稳定的铬碳化合物,从而有效锁定固溶碳原子,防止固溶碳原子随时间推移发生偏聚并导致性能波动。硅和锰元素的添加主要用来固溶强化并稳定奥氏体,为获得良好的延伸率与翻边成形性提供保障。铝的加入有助于脱氧并细化晶粒,进一步提升综合成形性能。在显微组织方面,高比例的铁素体作为柔软基体,确保热镀锌双相钢具备高的初始延伸率与无屈服平台特性,从而满足复杂成形与表面质量要求。一定量的马氏体与贝氏体作为硬质相均匀分布,提供必要的强度支撑,并有利于翻边成形。少量残余奥氏体能够在变形过程中诱发相变,增加成形塑性。在铁素体晶界及相界处弥散析出的微细铬碳化合物,直接发挥固定碳原子、抑制自然时效进程的核心作用。上述多相组织构成的性能优势,通过碳化物的时效抑制功能,在仓储与服役期间得以长期保持。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979755A_ABST
    Figure CN122979755A_ABST
Patent Text Reader

Abstract

The application relates to a 500MPa-grade natural-aging-resistant enhanced formability hot-dip galvanized dual-phase steel and a preparation method, and belongs to the technical field of steel preparation. The chemical composition of the hot-dip galvanized dual-phase steel is as follows in terms of mass fraction: C: 0.06%-0.12%, Si: 0.20%-0.50%, Mn: 1.05%-1.55%, Cr: 0.20%-0.60%, Al: 0.30%-0.70%, P<=0.015%, S<=0.0025%, and the rest is Fe and inevitable impurities; the microstructure of the hot-dip galvanized dual-phase steel is based on ferrite, and martensite and bainite are main hardening phases, and the volume fraction of residual austenite is not more than 8%; carbides are diffusely distributed on the grain boundaries of the ferrite and the phase boundaries of the ferrite and residual austenite and / or martensite; the size of the carbides is <=0.3 mu m. The natural-aging-resistant capability of the hot-dip galvanized dual-phase steel is improved through a continuous hot-dip galvanizing process of medium-carbon-chromium alloy component design and slow cooling section synergic control. The obtained hot-dip galvanized dual-phase steel maintains high strength, has formability and long-term stability, and meets the requirements of automobile outer plates on high flanging and durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of steel preparation technology, and in particular to 500MPa grade resistant to natural aging reinforced formable hot-dip galvanized duplex steel and its preparation method. Background Technology

[0002] With the continuous improvement of automotive lightweighting and safety standards, higher requirements are being placed on the material performance of exterior body panels. Traditional mild steel and low-alloy high-strength steel struggle to balance strength, formability, and lightweighting. Therefore, 500MPa-grade reinforced formable hot-dip galvanized duplex steel, which combines high strength with good formability, has become an important development direction. This type of steel, by introducing a certain amount of retained austenite into a ferrite-martensite matrix, can simultaneously improve strength and plasticity, and is expected to meet the comprehensive requirements of automotive exterior panels for lightweighting, dent resistance, and complex formability.

[0003] However, when applying 500MPa-grade reinforced formable hot-dip galvanized duplex steel to automotive outer panels, three mutually restrictive performance requirements must be met simultaneously: high hole-expanding formability, low sensitivity to natural aging, and stable high elongation without a yield plateau. Existing technical solutions often focus only on one or two of these aspects, making it difficult to systematically address the problem of mechanical property fluctuations in hot-dip galvanized duplex steel during the aging process from storage and transportation to stamping. This can easily lead to decreased stamping stability and surface defect risks, thus restricting the large-scale application of this type of steel in outer panels with high surface finish requirements.

[0004] To address the aforementioned challenges, existing approaches have varying focuses: some schemes aim to optimize the instant forming and hole-expanding properties of hot-dip galvanized duplex steel through composition and microstructure design, but lack systematic control over natural aging stability; others employ surface modification or mechanical straightening to attempt to improve aging behavior, but these methods often only produce short-term effects or may adversely affect the surface quality of the coating; still others pursue anti-aging properties through composition design such as ultra-low carbon or supersaturated precipitation, but this usually inevitably comes at the cost of sacrificing the strength of hot-dip galvanized duplex steel or significantly increasing costs. Summary of the Invention

[0005] This application provides a 500MPa grade, naturally aging resistant, reinforced hot-dip galvanized duplex steel and its preparation method to solve the following technical problem: how to achieve the unity of high flanging, high elongation and long-term aging resistance of hot-dip galvanized duplex steel. In a first aspect, embodiments of this application provide a 500MPa grade, naturally aging resistant, reinforced, formable hot-dip galvanized duplex steel. The chemical composition of the hot-dip galvanized duplex steel, by mass fraction, is: C: 0.06%~0.12%, Si: 0.20%~0.50%, Mn: 1.05%~1.55%, Cr: 0.20%~0.60%, Al: 0.30%~0.70%, P≤0.015%, S≤0.0025%, with the remainder being Fe and unavoidable impurities. The microstructure of the hot-dip galvanized duplex steel is based on ferrite, with martensite and bainite as the main hard reinforcing phases, and contains a residual austenite with a volume fraction of no more than 8%. Carbides are dispersedly distributed at the grain boundaries of the ferrite and at the phase boundaries between the ferrite and the retained austenite and / or martensite; the size of the carbides is ≤0.3μm.

[0006] Optionally, the volume fraction of ferrite is 65% to 78%, the sum of the volume fractions of martensite and bainite is 15% to 30%, and the volume fraction of retained austenite is 2% to 8%.

[0007] Optionally, the hot-dip galvanized duplex steel meets at least one of the following properties: yield strength of 290MPa~390MPa, tensile strength ≥500MPa, and elongation after fracture A. 80 ≥33%, pore expansion rate ≥40%, bake hardening value BH ≥65MPa; After two months of natural aging, the yield elongation Ae is 0, and the yield strength fluctuation is no more than 10 MPa.

[0008] Secondly, embodiments of this application provide a method for preparing the hot-dip galvanized duplex steel described in the first aspect, the method comprising: Molten steel with the following chemical composition is continuously cast to obtain a slab: C: 0.06%~0.12%, Si: 0.20%~0.50%, Mn: 1.05%~1.55%, Cr: 0.20%~0.60%, Al: 0.30%~0.70%, P≤0.015%, S≤0.0025%, with the remainder being Fe and unavoidable impurities; The slab is sequentially heated, homogenized, rough rolled, finish rolled, and coiled to obtain a hot-rolled coil. The hot-rolled coil is subjected to pickling, continuous hot-dip galvanizing and finishing in sequence to obtain hot-dip galvanized duplex steel; wherein, the continuous hot-dip galvanizing includes: a soaking section, a slow cooling section, a rapid cooling section, an over-aging section and a galvanizing section.

[0009] Optionally, the heating temperature is 1150℃~1250℃; the heat equalization time is 80min~100min.

[0010] Optionally, the entry temperature of the finishing mill is 1000℃~1100℃; the final rolling temperature of the finishing mill is 880℃~920℃; and the coiling temperature is 550℃~680℃.

[0011] Optionally, the belt speed for continuous hot-dip galvanizing is 90m / min to 120m / min.

[0012] Optionally, the temperature of the heat-spreading section is 780℃~830℃, and the heat-spreading time is 80s~110s; the temperature of the slow cooling section is 650℃~700℃.

[0013] Optionally, the temperature of the over-aging period is 465℃~480℃, and the time of the over-aging period is 50s~80s.

[0014] Optionally, the elongation of the finishing process is 0.6% to 0.8%.

[0015] Thirdly, an automotive exterior panel made of the hot-dip galvanized duplex steel described in the first aspect.

[0016] The technical solutions provided in this application have the following advantages compared with the prior art: This application provides a 500MPa grade, naturally aging-resistant, reinforced, formable hot-dip galvanized duplex steel and its preparation method. The chemical composition of the hot-dip galvanized duplex steel, by mass fraction, is: C: 0.06%~0.12%, Si: 0.20%~0.50%, Mn: 1.05%~1.55%, Cr: 0.20%~0.60%, Al: 0.30%~0.70%, P≤0.015%, S≤0.0025%, with the remainder being Fe and unavoidable impurities. The microstructure of the hot-dip galvanized duplex steel is based on ferrite, with martensite and bainite as the main hard reinforcing phases, and also contains retained austenite with a volume fraction not exceeding 8%. Carbides are dispersedly distributed at the grain boundaries of the ferrite and at the phase boundaries between the ferrite and retained austenite and / or martensite; the size of the carbides is ≤0.3μm. In terms of composition design, 0.06wt%~0.12wt% carbon and 0.20wt%~0.60wt% chromium provide the foundation for resistance to natural aging. An appropriate amount of carbon is essential to ensure the strength of hot-dip galvanized duplex steel. The added chromium can combine with carbon to form stable chromium-carbon compounds in subsequent processes, effectively locking in dissolved carbon atoms and preventing their segregation over time, which could lead to performance fluctuations. The addition of silicon and manganese is mainly used for solid solution strengthening and stabilizing austenite, ensuring good elongation and flanging formability. The addition of aluminum helps deoxidize and refine grains, further improving overall formability. In terms of microstructure, a high proportion of ferrite acts as a soft matrix, ensuring that hot-dip galvanized duplex steel possesses high initial elongation and no yield plateau characteristics, thus meeting complex forming and surface quality requirements. A certain amount of martensite and bainite, as hard phases, are evenly distributed, providing necessary strength support and facilitating flanging. A small amount of retained austenite can induce phase transformation during deformation, increasing formability. The fine chromium-carbon compounds dispersed at ferrite grain boundaries and phase boundaries play a crucial role in fixing carbon atoms and inhibiting the natural aging process. The performance advantages of this multiphase microstructure are maintained over a long period of time during storage and service through the aging-inhibiting function of the carbides.

[0017] In summary, the combination of chromium and carbon elements lays the foundation for aging resistance and formability; furthermore, the microstructure design, consisting of a ferrite matrix, hard phases, retained austenite, and grain boundary carbides, transforms the compositional potential into practical performance. Ultimately, a balance between high flanging performance, high elongation, and long-term resistance to natural aging is successfully achieved at a strength level of 500 MPa. Attached Figure Description

[0018] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.

[0019] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, those skilled in the art can obtain other drawings based on these drawings without any creative effort.

[0020] Figure 1 A flowchart illustrating the preparation method of 500MPa grade resistant to natural aging reinforced hot-dip galvanized duplex steel provided in the embodiments of this application; Figure 2 Microstructure of 500MPa grade resistant to natural aging, reinforced formable hot-dip galvanized duplex steel provided in the embodiments of this application; in the figure, M: martensite, F: ferrite, B: bainite, A: retained austenite; Figure 3 Engineering stress-strain curve of 500MPa grade natural aging resistant reinforced hot-dip galvanized duplex steel provided in Embodiment 3 of this application; Figure 4 The engineering stress-strain curve of the 500MPa grade reinforced formable hot-dip galvanized duplex steel after two months of natural aging is provided as Comparative Example 2 of this application. Detailed Implementation

[0021] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only some, not all, of the embodiments of this application. All other embodiments obtained by those skilled in the art based on the embodiments of this application without creative effort are within the scope of protection of this application.

[0022] The range descriptions used herein, such as numerical ranges and proportional ranges, include all possible sub-ranges and single numerical values ​​within that range. For example, the range descriptions of "1 to 6" or "1~6" cover all sub-ranges between 1 and 6 (such as 1 to 3, 2 to 5, etc.) and single numbers (such as 1, 2, 3, 4, 5, 6). Unless otherwise specified, the terms "including" and "contains" used herein mean "including but not limited to"; relational terms such as "first" and "second" are used only to distinguish different entities or operations and do not imply an actual order or relationship. "And / or" indicates that multiple situations can exist individually or simultaneously. Expressions such as "at least one," "multiple," and "at least one" refer to any combination of the corresponding objects, including combinations of single or multiple objects. The proportional relationships mentioned herein, such as mass ratios and molar ratios, should be understood as the correspondence between the first and second terms of a proportional formula, according to the order of description. The raw materials, reagents, instruments, and equipment used herein can all be obtained through commercial purchase or prepared using existing methods.

[0023] In a first aspect, embodiments of this application provide a 500MPa grade, naturally aging resistant, reinforced, formable hot-dip galvanized duplex steel. The chemical composition of the hot-dip galvanized duplex steel, by mass fraction, is: C: 0.06%~0.12%, Si: 0.20%~0.50%, Mn: 1.05%~1.55%, Cr: 0.20%~0.60%, Al: 0.30%~0.70%, P≤0.015%, S≤0.0025%, with the remainder being Fe and unavoidable impurities. The positive effects of limiting the carbon (C) mass fraction to 0.06%~0.12% are as follows: C is a fundamental element providing solid solution strengthening and bake hardening potential. The C mass fraction is necessary to ensure that hot-dip galvanized duplex steel reaches a strength of 500 MPa, and it also provides a carbon source for the formation of stable carbides with elements such as Cr in subsequent processes. When the C mass fraction is too low, the strength of the hot-dip galvanized duplex steel will be insufficient; when the C mass fraction is too high, it will be detrimental to the plasticity and aging resistance of the hot-dip galvanized duplex steel. For example, the C mass fraction can be 0.06%, 0.08%, 0.10%, 0.12%, etc.

[0024] The positive effects of limiting the Si mass fraction to 0.20%~0.50% include: Si achieves solid solution strengthening while ensuring surface quality and coating control in the continuous hot-dip galvanizing process of dual-phase steel. The lower limit of the Si mass fraction ensures the necessary strength contribution, while the upper limit prevents excessive Si segregation to the surface during annealing, thus effectively suppressing the adverse effects of Si on the hot-dip galvanizing alloying process and the excessive formation of surface oxides. For example, the Si mass fraction can be 0.20%, 0.30%, 0.40%, 0.50%, etc.

[0025] The positive effects of limiting the Mn mass fraction to 1.05%~1.55% are as follows: Mn is a major solid solution strengthening element used to stabilize austenite, improve the hardenability of hot-dip galvanized duplex steel, and ensure the formation of the necessary hard martensite or bainite phases during the cooling process after continuous annealing, thereby guaranteeing the strength of the hot-dip galvanized duplex steel. For example, the Mn mass fraction can be 1.05%, 1.15%, 1.25%, 1.35%, 1.45%, 1.55%, etc.

[0026] The positive effects of limiting the Cr mass fraction to 0.20%~0.60%: Cr is a core element for achieving excellent resistance to natural aging. Cr has a strong affinity for C, and under specific process windows of continuous annealing, Cr and C can effectively promote the formation of fine and stable carbides (such as Cr...). 23C6) is formed and fully analyzed. This carbon atom fixation mechanism minimizes the number of freely mobile solid-solid carbon atoms at room temperature, thereby reducing the natural aging process at its source and preventing the yield plateau from recurring after storage. When the mass fraction of Cr is low, natural aging cannot be effectively suppressed; when the mass fraction of Cr is too high, the strength of the hot-dip galvanized duplex steel is too high, which is not conducive to subsequent outer plate forming. For example, the mass fraction of Cr can be 0.20%, 0.30%, 0.40%, 0.50%, 0.60%, etc.

[0027] The positive effects of limiting the Al mass fraction to 0.30%~0.70% include: Al effectively deoxidizes and refines grains, ensuring smooth galvanizing processes and coating quality. As a strong deoxidizer, the lower limit of Al mass fraction ensures the cleanliness of the molten steel; simultaneously, Al refines the microstructure, which is beneficial to improving the overall performance of hot-dip galvanized duplex steel. Strictly controlling the upper limit of Al mass fraction is mainly to prevent the formation of an excessively thick and dense alumina film on the surface of hot-dip galvanized duplex steel in an annealing atmosphere, as this alumina film severely degrades the wettability and adhesion of the coating. For example, the Al mass fraction can be 0.30%, 0.40%, 0.50%, 0.60%, 0.70%, etc.

[0028] The positive effect of limiting the mass fraction of phosphorus (P) to ≤0.015%: P is a harmful element, and it is necessary to minimize the harmful segregation of P at grain boundaries to avoid serious damage to the plasticity of hot-dip galvanized duplex steel. For example, the mass fraction of P can be 0.005%, 0.010%, 0.015%, etc.

[0029] The positive effects of limiting the mass fraction of sulfur (S) to ≤0.0025%: S is a harmful element, and it is necessary to fundamentally reduce the formation of MnS-type inclusions to eliminate the risk of these inclusions becoming microcrack initiators during subsequent forming processes. For example, the mass fraction of S can be 0.0005%, 0.0010%, 0.0015%, 0.0020%, 0.0025%, etc.

[0030] Fe is a matrix element, and the specific content / range of Fe can be obtained through the upper and lower limit formulas of the component, that is: The sum of the percentages of all components in a composition should equal 100%, and the content ranges of several components should meet the following conditions: the upper limit of a certain component + the lower limit of other components ≤ 100; the lower limit of a certain component + the upper limit of other components ≥ 100. Furthermore, the specific content of Fe is made up to 100% by the actual detected values ​​of the other chemical components mentioned above, together with any unlisted active elements and / or impurity elements, and Fe must constitute the absolute proportion as a matrix element.

[0031] The microstructure of the hot-dip galvanized duplex steel is based on ferrite, with martensite and bainite as the main hard reinforcing phases, and also contains a residual austenite with a volume fraction of no more than 8%.

[0032] The microstructure of hot-dip galvanized duplex steel is based on ferrite, ensuring excellent elongation and a yield plateau-free characteristic, thus meeting the stringent requirements of high plasticity and surface quality in complex stamping processes. Martensite and bainite, as the main hard reinforcing phases, are uniformly distributed, providing necessary strength support for the hot-dip galvanized duplex steel. Together with the ferrite matrix, they form a multiphase structure conducive to stress dispersion, which is key to achieving high flanging performance. A small amount of retained austenite can undergo transformation-induced plasticity during forming, further increasing the uniform deformation capacity of the hot-dip galvanized duplex steel. Carbides are dispersedly distributed at the grain boundaries of the ferrite and at the phase boundaries between the ferrite and the retained austenite and / or martensite; the size of the carbides is ≤0.3μm.

[0033] Carbides, with a size ≤0.3 μm, are dispersed at the grain boundaries of ferrite and at the phase boundaries between ferrite and retained austenite and / or martensite. These carbides are actively formed during the intermediate-temperature slow cooling stage. Their core function is to act as carbon atom traps, effectively fixing or consuming most of the free carbon atoms in the matrix. The presence of these stable carbides significantly reduces the solute carbon concentration that triggers natural aging at its source. These carbides provide direct microstructural evidence for the non-recurrence of the yield plateau and reduced fluctuations in mechanical properties of hot-dip galvanized duplex steel after natural aging, and represent the fundamental mechanism for achieving these effects. For example, the carbide size can be 0.1 μm, 0.2 μm, 0.3 μm, etc.

[0034] In some embodiments, the volume fraction of ferrite is 65% to 78%, the sum of the volume fractions of martensite and bainite is 15% to 30%, and the volume fraction of retained austenite is 2% to 8%.

[0035] Ferrite, with a volume fraction of 65%–78%, constitutes the soft phase matrix of the microstructure. Ferrite is the primary contributor to plasticity, and a sufficient ferrite volume fraction is fundamental to ensuring the elongation after fracture and good overall formability of hot-dip galvanized duplex steel. When the ferrite volume fraction is below 65%, the uniform elongation capability of hot-dip galvanized duplex steel will significantly decrease, making it difficult to meet the high plasticity requirements for outer sheet forming; when the ferrite volume fraction is above 78%, hot-dip galvanized duplex steel cannot guarantee reaching the tensile strength threshold of 500 MPa. For example, the ferrite volume fraction can be 65%, 70%, 75%, etc.

[0036] The combined volume fraction of martensite and bainite is 15%–30%. As the primary strengthening phases, martensite and bainite provide the necessary strength to ensure that hot-dip galvanized duplex steel achieves mechanical properties at the 500 MPa level. The introduction of bainite also reduces the hardness difference between martensite and ferrite, which is crucial for balancing the strength and formability of hot-dip galvanized duplex steel. For example, the combined volume fraction of martensite and bainite can be 15%, 20%, 25%, 30%, etc.

[0037] The volume fraction of retained austenite is 2% to 8%. This proportion of retained austenite can undergo phase transformation-induced plasticity during plastic deformation, providing additional plasticity reserves for hot-dip galvanized duplex steel and helping to improve uniform elongation. Simultaneously, controlling the volume fraction of retained austenite within this range can avoid performance instability caused by excessively high retained austenite volume fraction, prevent the increase of crack initiation points during hole expansion, and thus prevent a significant decline in hole expansion performance. For example, the volume fraction of retained austenite can be 2%, 4%, 6%, 8%, etc.

[0038] In some embodiments, the hot-dip galvanized duplex steel satisfies at least one of the following properties: yield strength of 290 MPa to 390 MPa, tensile strength ≥ 500 MPa, and elongation after fracture A. 80 ≥33%, pore expansion rate ≥40%, bake hardening value BH ≥65MPa; After two months of natural aging, the yield elongation Ae is 0, and the yield strength fluctuation is no more than 10 MPa.

[0039] Yield strength: The stress value at which a material begins to undergo significant plastic deformation. A yield strength between 290 MPa and 390 MPa ensures that hot-dip galvanized duplex steel exhibits smooth rheological behavior in the early stages of stamping, avoiding excessively high yield stress that could lead to forming difficulties, and also preventing insufficient dent resistance that might result from an excessively low yield point. For example, yield strengths can be 290 MPa, 310 MPa, 330 MPa, 350 MPa, 370 MPa, 390 MPa, etc. Tensile strength: The maximum stress value that a material can withstand before tensile fracture. A tensile strength ≥ 500 MPa is a core strength guarantee for achieving lightweight automotive components, providing the necessary structural strength and collision safety for the final part, while also providing sufficient base strength reserves for flanging. For example, tensile strengths can be 500 MPa, 550 MPa, 600 MPa, etc. Elongation after fracture (A80): The plastic elongation of a specimen after fracture, measured at a gauge length of 80 mm, is a key indicator for evaluating the overall uniform deformation capability of a material. An elongation after fracture (A80) ≥ 33% ​​indicates that hot-dip galvanized duplex steel has excellent potential for deep drawing and stretching, meeting the stamping requirements for complex shapes in automotive exterior body panels. Examples of A80 values ​​are 33%, 35%, 37%, and 39%. Hole expansion rate: A specific indicator for evaluating the edge expansion or flanging capability of a material. A higher value indicates stronger resistance to edge cracking during hole flanging. A hole expansion rate ≥ 40% directly corresponds to excellent flanging performance, ensuring a high yield and forming limit when manufacturing parts with bosses, reinforcing ribs, or flanging features. Examples of hole expansion rates are 40%, 42%, 44%, 46%, 48%, and 50%. Bake hardening value (BH): The increment of the material's yield strength after a specific simulated coating baking heat treatment. A bake hardening value (BH) ≥ 65 MPa means that the strength of the part is significantly improved after stamping and painting / baking. This increased strength enhances the dent resistance of the final component and improves the retention of surface quality on the vehicle body. For example, the bake hardening value (BH) can be 65 MPa, 67 MPa, 69 MPa, etc.

[0040] Figure 1 A flowchart illustrating the preparation method of 500MPa grade resistant to natural aging reinforced hot-dip galvanized duplex steel provided in this application embodiment.

[0041] Please see Figure 1 Secondly, this application provides a method for preparing the hot-dip galvanized duplex steel described in the first aspect, the method comprising: S1. Continuously cast molten steel with the following chemical composition to obtain a slab: C: 0.06%~0.12%, Si: 0.20%~0.50%, Mn: 1.05%~1.55%, Cr: 0.20%~0.60%, Al: 0.30%~0.70%, P≤0.015%, S≤0.0025%, with the remainder being Fe and unavoidable impurities; S2. The slab is sequentially heated, homogenized, rough rolled, finish rolled, and coiled to obtain a hot-rolled coil; S3. The hot-rolled coil is subjected to pickling, continuous hot-dip galvanizing and finishing in sequence to obtain hot-dip galvanized duplex steel; wherein, the continuous hot-dip galvanizing includes: a soaking section, a slow cooling section, a rapid cooling section, an over-aging section and a galvanizing section.

[0042] In some embodiments, the heating temperature is 1150℃~1250℃; the heat equalization time is 80min~100min.

[0043] The heating temperature is between 1150℃ and 1250℃. This temperature range is designed to ensure that key alloying elements, such as chromium and carbon, are fully dissolved in the austenitic matrix. The soaking time is between 80 min and 100 min. After heating, sufficient soaking time ensures that the temperature of the slab cross-section is homogenized and that the dissolved alloying elements diffuse sufficiently. For example, the heating temperature can be 1150℃, 1200℃, 1250℃, etc.; the soaking time can be 80 min, 85 min, 90 min, 95 min, 100 min, etc.

[0044] In some embodiments, the entry temperature of the finishing mill is 1000℃~1100℃; the final rolling temperature of the finishing mill is 880℃~920℃; and the coiling temperature is 550℃~680℃.

[0045] The entry temperature of the finishing mill is between 1000℃ and 1100℃ to ensure that the slab has sufficient temperature and plasticity when entering the finishing mill, guaranteeing smooth rolling deformation. This also avoids excessively high entry temperatures that would increase the difficulty of process control, providing stable initial conditions for achieving the desired final rolling temperature. For example, the entry temperature of the finishing mill can be 1000℃, 1020℃, 1040℃, 1060℃, 1080℃, or 1100℃. The final rolling temperature of the finishing mill is between 880℃ and 920℃. A final rolling temperature above 920℃ can easily lead to coarse grains in the hot-rolled coil; a final rolling temperature below 880℃ will significantly increase the deformation resistance of the hot-rolled coil and easily produce a mixed-grain structure. Both of these situations are detrimental to providing hot-rolled coils with uniform microstructure for subsequent processes, thus affecting the overall forming performance and long-term stability of hot-dip galvanized duplex steel. For example, the finishing rolling temperature can be 880℃, 890℃, 900℃, 910℃, 920℃, etc.

[0046] The coiling temperature is between 550℃ and 680℃. This temperature range avoids the flattening defect caused by excessively high temperatures in the hot-rolled coil, while preventing the formation of hard phase structures such as bainite or martensite in the hot-rolled coil at excessively low temperatures. Controlling the coiling temperature ensures that the hot-dip galvanized duplex steel has good subsequent cold rolling workability and lays the foundation for obtaining a uniform, high-quality finished product structure. For example, the coiling temperature can be 550℃, 570℃, 590℃, 610℃, 630℃, 650℃, 670℃, etc.

[0047] In some embodiments, the belt speed for continuous hot-dip galvanizing is 90 m / min to 120 m / min.

[0048] The belt speed for continuous hot-dip galvanizing is between 90 m / min and 120 m / min. This speed range ensures sufficient residence time for the hot-rolled coil in the slow cooling section, providing the necessary atomic diffusion conditions for the adequate nucleation and growth of carbides. These conditions are key process controls for achieving effective locking of dissolved carbon atoms and improving the resistance of hot-dip galvanized duplex steel to natural aging. A belt speed below 90 m / min will impair production efficiency and economy; a belt speed above 120 m / min will lead to insufficient carbide precipitation, weakening the long-term performance stability of the hot-dip galvanized duplex steel. For example, the belt speed for continuous hot-dip galvanizing can be 90 m / min, 100 m / min, 110 m / min, 120 m / min, etc.

[0049] In some embodiments, the temperature of the heat-spreading section is 780℃~830℃, and the heat-spreading time is 80s~110s; the temperature of the slow cooling section is 650℃~700℃.

[0050] The soaking zone aims to recrystallize the microstructure after cold rolling to eliminate work hardening and achieve crucial partial austenitization. The temperature in the soaking zone is controlled between 780℃ and 830℃, and the soaking time is controlled between 80s and 110s. During this time, a suitable ratio of austenite and ferrite two-phase microstructure is formed in the hot-dip galvanized duplex steel. In the subsequent slow cooling process, some austenite preferentially transforms into clean primary ferrite. Since the solubility of elements such as carbon, manganese, and chromium in austenite is much higher than in ferrite, carbon, manganese, and chromium are selectively enriched within the remaining austenite phase, significantly increasing the local solute concentration. If the temperature or duration of the soaking zone is too high, it will result in an excessively high austenite ratio and coarse grains, thereby impairing the uniform elongation and toughness of the hot-dip galvanized duplex steel. Conversely, if the temperature or duration of the soaking zone is too low, it will lead to insufficient austenitization and poor solute enrichment, directly reducing the amount of carbides available for fixing carbon atoms and weakening the long-term stability of the hot-dip galvanized duplex steel. For example, the temperature of the soaking zone can be 780℃, 790℃, 800℃, 810℃, 820℃, 830℃, etc.; and the soaking time can be 80s, 90s, 100s, 110s, etc.

[0051] The temperature in the slow cooling section is between 650℃ and 700℃. Primary ferrite nucleates and grows from the solute-enriched austenite. Because primary ferrite has extremely low carbon solubility, it displaces most of the carbon atoms within the body to the phase boundaries and retained austenite. Chromium, added to the composition of this invention, is a strong carbide-forming element. Chromium can rapidly combine with the aforementioned highly enriched carbon, thereby forming a large number of fine and thermodynamically stable carbides at the phase boundaries and in the austenite. Chromium effectively locks in most of the dissolved carbon atoms. When the temperature in the slow cooling section is below 650℃, the diffusion ability of carbon and chromium atoms is severely insufficient, resulting in slow precipitation kinetics. This leads to insufficient carbide precipitation, leaving a large number of carbon atoms remaining in the solid solution, thus failing to improve the resistance to natural aging of the hot-dip galvanized duplex steel. When the temperature in the slow cooling section exceeds 700℃, the carbides coarsen, disrupting the strength balance of the hot-dip galvanized duplex steel structure. For example, the temperature of the slow cooling section can be 650℃, 660℃, 670℃, 680℃, 690℃, 700℃, etc.

[0052] In some embodiments, the temperature of the over-aging period is 465°C to 480°C, and the time of the over-aging period is 50s to 80s.

[0053] The over-aging stage aims to protect the stable carbides formed in the slow cooling stage from damage, ensuring the long-term carbon fixation effect and thus improving the resistance of hot-dip galvanized duplex steel to natural aging. The over-aging temperature is between 465℃ and 480℃, and the over-aging time is between 50s and 80s. This temperature and time range allows some of the carbon-rich residual austenite to transform into bainite, reducing the hardness difference between the martensite and ferrite phases in the hot-dip galvanized duplex steel, which helps improve the uniform deformation capacity of the hot-dip galvanized duplex steel and further enhances its overall formability. When the over-aging temperature exceeds 480℃, the excessively high temperature may cause coarsening or even partial dissolution of the precipitated carbides, thereby weakening the carbon fixation effect; when the over-aging temperature is below 465℃ or the time is less than 50s, the microstructure transformation of the hot-dip galvanized duplex steel may be insufficient. For example, the temperature of the over-aging period can be 465℃, 470℃, 475℃, 480℃, etc.; the time of the over-aging period can be 50s, 60s, 70s, 80s, etc.

[0054] In some embodiments, the elongation of the finishing process is 0.6% to 0.8%.

[0055] The elongation of the finishing process is between 0.6% and 0.8%. This range is designed to achieve two optimizations: First, by introducing moderate plastic deformation, the initial yield plateau of the hot-dip galvanized duplex steel is effectively eliminated, preventing surface defects such as slip lines during subsequent stamping and ensuring the surface quality of the outer panel. Second, an appropriate amount of uniform dislocations are introduced into the matrix to preserve the necessary bake-hardening potential of the hot-dip galvanized duplex steel while ensuring its resistance to natural aging. When the elongation of the finishing process is below 0.6%, the yield plateau is not completely eliminated and the introduced dislocation density is insufficient, resulting in a low bake-hardening value. When the elongation of the finishing process exceeds 0.8%, excessive work hardening occurs, significantly depleting the initial plastic reserve of the hot-dip galvanized duplex steel and impairing its overall formability. For example, the elongation of the finishing process can be 0.6%, 0.7%, 0.8%, etc.

[0056] Thirdly, an automotive exterior panel made of the hot-dip galvanized duplex steel described in the first aspect.

[0057] The product prepared by the method for preparing hot-dip galvanized duplex steel is the aforementioned hot-dip galvanized duplex steel. Since the method for preparing hot-dip galvanized duplex steel adopts some or all of the technical solutions of the embodiments of hot-dip galvanized duplex steel, it has at least all the beneficial effects brought about by the technical solutions of the aforementioned embodiments, which will not be elaborated here.

[0058] The present application is further illustrated below with reference to specific embodiments. Experimental methods in the following embodiments that do not specify specific conditions are generally determined according to national standards / industry standards / the disclosure herein; if there are no corresponding national standards / industry standards / the disclosure herein, they are performed according to generally accepted international standards, conventional conditions, or conditions recommended by the manufacturer.

[0059] The chemical composition (mass percentage / %) of the examples and comparative examples is shown in Table 1.

[0060] Table 1

[0061] Based on the chemical composition of the examples and comparative examples, this embodiment also provides a method for preparing 500MPa grade, naturally aging resistant, reinforced, formable hot-dip galvanized duplex steel, comprising the following steps: The molten steel with the chemical composition described in Table 1 was continuously cast to obtain a slab; The slab is heated, homogenized, rough rolled, finish rolled and coiled in sequence to obtain a hot-rolled coil. Hot-rolled coils are sequentially pickled, continuously hot-dip galvanized, and finished to obtain hot-dip galvanized duplex steel with a thickness of 0.6 mm. The continuous hot-dip galvanizing process includes: a soaking zone, a slow cooling zone, a rapid cooling zone, an aging zone, and a galvanizing zone. The process parameters are shown in Tables 2 and 3.

[0062] The process parameters for the examples and comparative examples are shown in Table 2.

[0063] Table 2

[0064] The process parameters for the examples and comparative examples are shown in Table 3.

[0065] Table 3

[0066] The microstructure of hot-dip galvanized duplex steel was detected and analyzed using scanning electron microscopy (SEM), electron backscatter diffraction (EBSD), and X-ray diffraction (XRD). Simultaneously, the mechanical properties, porosity, and bake hardening value of the hot-dip galvanized duplex steel were determined using a tensile testing machine and a forming testing machine. The microstructure characteristics and overall properties of Examples 1-4 and Comparative Examples 1-3 are shown in Tables 4 and 5.

[0067] Table 4

[0068] Table 5

[0069] The overall performance of the examples and comparative examples after 2 months is shown in Table 6.

[0070] Table 6

[0071] The data tables above provide a clear comparison of the differences between various embodiments and comparative examples. The following conclusions can be drawn: As can be seen from the data in Table 4, the hot-dip galvanized duplex steel provided in this application has a ferrite volume fraction of 68%~78%, a martensite and bainite volume fraction of 15%~30%, a retained austenite volume fraction of 2%~8%, and a maximum carbide size of 0.1μm~0.3μm.

[0072] As can be seen from the data in Tables 5 and 6, the hot-dip galvanized duplex steel provided in the embodiments of this application has a yield strength of 301MPa~329MPa, a tensile strength of 521MPa~543MPa, and an elongation after fracture A. 80 The yield strength is 33%~34.5%, the porosity is 40%~53%, the bake hardening value is 65MPa~76MPa, and the surface quality reaches FD grade. After two months of natural aging, the yield strength is 311MPa~337MPa, the tensile strength is 522MPa~545MPa, and the elongation after fracture is A. 80 The yield strength is 31.5%~33%, the elongation at break is 0, and there is no yield plateau.

[0073] As can be seen from Examples 1-4, through the synergistic design of specific chemical components and the control of core process parameters, Examples 1-4 can achieve a yield strength of 290MPa~390MPa, a tensile strength ≥500MPa, and an elongation after fracture (A) in the initial state. 80 With excellent comprehensive properties including ≥33%, bake hardening value BH≥65MPa, and expansion rate≥40%, it fully meets the performance and surface quality requirements of 500MPa grade reinforced formable hot-dip galvanized duplex steel high-strength outer sheet. Crucially, after two months of natural aging, the yield strength increase of Examples 1-4 is ≤10MPa, the elongation after fracture decreases by 1%, and no yield elongation was observed in any of the examples, demonstrating excellent resistance to natural aging. These results prove that Examples 1-4 of this application successfully achieve a balance between high flanging performance, high elongation, and long-term resistance to aging, making them particularly suitable for the production of automotive door outer panels (such as concealed door handles) and other parts with stringent requirements for flanging forming and long-term dimensional stability.

[0074] As can be seen from Comparative Example 1, since the mass fraction of carbon is 0.13%, which exceeds the range designed in this application, although the process execution target value is still within the range of this invention, the slow cooling section and the over-aging section cannot fix enough carbon atoms, resulting in obvious natural aging phenomenon, specifically manifested as an increase in yield strength of about 20 MPa and a loss of plasticity of 3%.

[0075] As shown in Comparative Example 2, the mass fraction of chromium is 0, which is below the design range of this application. Chromium is a core element for achieving excellent resistance to natural aging. Under the specific process window of continuous hot-dip galvanizing, chromium can effectively promote the formation of fine and stable carbides (such as Cr). 23 C6) was analyzed and thus minimized the number of freely mobile solid-solid carbon atoms at room temperature, thereby inhibiting the natural aging process at its source and preventing the yield plateau from recurring after storage. Due to the lack of chromium in Comparative Example 2, although no yield plateau appeared after the production line was completed, the aging phenomenon was obvious after 2 months of natural aging, and the yield plateau reappeared.

[0076] As shown in Comparative Example 3, when the finishing elongation is less than 0.6%, although the unwound coil eliminates the yield plateau at the time of unwound, it fails to introduce sufficient dislocation density to pin the solid solution carbon atoms during the finishing process, causing the carbon atoms to still freely agglomerate during the aging period, and the yield plateau reappears after storage.

[0077] Appendix Figures 2-4 Detailed explanation: Figure 2 Microstructure of 500MPa grade, naturally age-resistant, reinforced, formable hot-dip galvanized duplex steel provided in this application embodiment. According to... Figure 2 It can be seen that ferrite is uniformly distributed over a large area as the matrix, while martensite and bainite are dispersed at the ferrite grain boundaries as hard reinforcing phases. At the same time, a small amount of residual austenite exists, and a large number of fine carbides are dispersed and precipitated at the phase boundaries and grain boundaries.

[0078] Figure 3 The engineering stress-strain curve of the 500MPa grade, naturally age-resistant, reinforced hot-dip galvanized duplex steel provided in Embodiment 3 of this application is shown. Figure 3 It can be seen that the tensile curve of Example 3 has no obvious yield plateau, which meets the requirements of automotive outer panels for the surface quality of the formed surface; the post-fracture engineering strain exceeds 30%, and the corresponding post-fracture elongation reaches the design requirement level, indicating that hot-dip galvanized duplex steel has excellent uniform plastic deformation ability; the tensile strength is stably maintained above 500MPa, which meets the strength requirements of 500MPa grade hot-dip galvanized duplex steel.

[0079] Figure 4 The image shows the engineering stress-strain curves of the 500MPa grade reinforced formable hot-dip galvanized duplex steel after two months of natural aging, as provided in Comparative Example 2 of this application. According to... Figure 4It can be seen that the yielding stage of Comparative Example 2 showed clear yield teeth, indicating that yield elongation had occurred. This characteristic directly leads to slip line defects on the surface of the part during subsequent stamping, failing to meet the surface quality requirements of automotive outer panels. Furthermore, the post-fracture engineering strain of this specimen was less than 30%, and the post-fracture elongation was significantly reduced compared to the initial state, indicating significant fluctuations in mechanical properties and insufficient resistance to natural aging for use.

[0080] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages: (1) Comprehensive performance breakthrough: Through the synergistic effect of specific chromium composition design and slow cooling process that promotes carbide precipitation, the concentration of free carbon atoms that cause natural aging is significantly reduced from the source; after 2 months of natural aging, hot-dip galvanized duplex steel can still guarantee no yield plateau, yield strength fluctuation ≤10MPa, and elongation after fracture A 80 Maintaining a strength of ≥33%, while achieving an initial tensile strength of ≥500MPa and a porosity of ≥40%, it successfully achieves a synergistic unity of high strength, high flanging ability, and high resistance to natural aging.

[0081] (2) Strong stamping stability: By actively forming thermodynamically stable chromium carbides to lock free carbon atoms, the room temperature structure of hot-dip galvanized duplex steel is more stable, which can ensure that the mechanical properties of hot-dip galvanized duplex steel are consistent for several weeks or even months before stamping. This fundamentally avoids mass production quality problems such as stamping parameter failure and slip lines on the surface of parts caused by aging, and provides a guarantee for the stable production of downstream OEMs.

[0082] (3) Taking into account multiple performance requirements: The surface quality of the coating in all embodiments meets the FD grade required for automotive outer panels, satisfying the stringent appearance requirements of high-end car bodies; at the same time, by precisely controlling the elongation rate of the finishing process to 0.6%~0.8%, while eliminating the initial yield plateau, a moderate dislocation density is introduced, allowing hot-dip galvanized dual-phase steel to obtain a bake hardening value of more than 65MPa while maintaining high resistance to aging, leaving sufficient space for the strength improvement of parts after coating and baking.

[0083] (4) Excellent process economy: The core process parameters of this application are all within the adjustable range of the existing continuous hot-dip galvanizing production line. There is no need to modify the existing production line. The process is mature and the cost is controllable. The hot-dip galvanized duplex steel prepared can meet the usage requirements of automotive exterior parts such as doors, side panels, and hoods with complex flange structures. It can not only help achieve the goal of lightweighting the car body, but also simplify the supply chain inventory management with its excellent anti-aging stability, effectively improving the overall production efficiency and parts qualification rate.

[0084] (5) Broad application prospects: Hot-dip galvanized duplex steel has both excellent immediate use performance and long-term service stability. The process is mature and controllable, and it has important application value and broad market prospects in the field of high-end automotive outer panels.

[0085] The above description is merely a specific embodiment of this application, enabling those skilled in the art to understand or implement this application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this application. Therefore, this application is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features claimed in this application.

Claims

1. A 500MPa grade, naturally aging-resistant, reinforced, formable hot-dip galvanized duplex steel, characterized in that, The chemical composition of the hot-dip galvanized duplex steel, by mass fraction, is as follows: C: 0.06%~0.12%, Si: 0.20%~0.50%, Mn: 1.05%~1.55%, Cr: 0.20%~0.60%, Al: 0.30%~0.70%, P≤0.015%, S≤0.0025%, with the remainder being Fe and unavoidable impurities; The microstructure of the hot-dip galvanized duplex steel is based on ferrite, with martensite and bainite as the main hard reinforcing phases, and contains a residual austenite with a volume fraction of no more than 8%. Carbides are dispersedly distributed at the grain boundaries of the ferrite and at the phase boundaries between the ferrite and the retained austenite and / or martensite; the size of the carbides is ≤0.3μm.

2. The hot-dip galvanized duplex steel according to claim 1, characterized in that, The volume fraction of ferrite is 65%~78%, the sum of the volume fractions of martensite and bainite is 15%~30%, and the volume fraction of retained austenite is 2%~8%.

3. The hot-dip galvanized duplex steel according to claim 1, characterized in that, The hot-dip galvanized duplex steel meets at least one of the following properties: yield strength of 290MPa~390MPa, tensile strength ≥500MPa, and elongation after fracture A. 80 ≥33%, pore expansion rate ≥40%, bake hardening value BH ≥65MPa; After two months of natural aging, the yield elongation Ae is 0, and the yield strength fluctuation is no more than 10 MPa.

4. A method for preparing hot-dip galvanized duplex steel according to any one of claims 1 to 3, characterized in that, The method includes: Molten steel having the chemical composition described in any one of claims 1 to 3 is continuously cast to obtain a slab; The slab is sequentially heated, homogenized, rough rolled, finish rolled, and coiled to obtain a hot-rolled coil. The hot-rolled coil is subjected to pickling, continuous hot-dip galvanizing and finishing in sequence to obtain hot-dip galvanized duplex steel; wherein, the continuous hot-dip galvanizing includes: a soaking section, a slow cooling section, a rapid cooling section, an over-aging section and a galvanizing section.

5. The method according to claim 4, characterized in that, The heating temperature is 1150℃~1250℃; the heat equalization time is 80min~100min.

6. The method according to claim 4, characterized in that, The entry temperature of the finishing mill is 1000℃~1100℃; the finishing temperature of the finishing mill is 880℃~920℃; and the coiling temperature is 550℃~680℃.

7. The method according to claim 4, characterized in that, The belt speed for continuous hot-dip galvanizing is 90m / min to 120m / min; The temperature of the heat-spreading section is 780℃~830℃, and the heat-spreading time is 80s~110s; the temperature of the slow cooling section is 650℃~700℃.

8. The method according to claim 4, characterized in that, The temperature of the over-aging period is 465℃~480℃, and the time of the over-aging period is 50s~80s.

9. The method according to claim 4, characterized in that, The elongation of the polished surface is 0.6%~0.8%.

10. An automotive exterior panel, characterized in that, Made of hot-dip galvanized duplex steel as described in any one of claims 1 to 3.